Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1152/ajpgi.1998.275.6.g1353
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in inflammation-induced suppression of secretion in a mouse model of acute colitis

Abstract: The role of nitric oxide (NO) derived from the inducible isoform of NO synthase (iNOS) in epithelial transport dysfunction was studied in a model of colitis induced in mice by intrarectal 2,4,6-trinitrobenzenesulfonic acid in 30% ethanol. Expression of iNOS mRNA was determined by RT-PCR. Electrolyte transport studies were conducted in Ussing chambers in which segments of inflamed colon were incubated with or without the selective iNOS inhibitorl- N 6-(1-iminoethyl)lysine (l-NIL). Seven days after the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 38 publications
2
59
0
1
Order By: Relevance
“…We previously showed that cholinergic control of ion transport is perturbed in tissue from mice with DSS-induced colitis (38), complementing observations from other studies (21,34). However, the DSS model is intriguing, because CCh produced a sustained reduction in I sc , rather than a diminished transient increase in I sc observed in other models, such as those evoked by 2,4,6-trinitrobenzenesulfonic acid, 2,4-dinitrobenzenesulfonic acid (21,34), or oxazolone (unpublished observation). Underlying differences in the models may contribute to this discrepancy; for example, 2,4,6-trinitrobenzenesulfonic acid and 2,4-dinitrobenzenesulfonic acid elicit a polarized Th1-type inflammatory response and oxazolone produces a Th2-type response, whereas DSSinduced colitis involves a Th1-and a Th2-type inflammatory profile (reviewed in Ref.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We previously showed that cholinergic control of ion transport is perturbed in tissue from mice with DSS-induced colitis (38), complementing observations from other studies (21,34). However, the DSS model is intriguing, because CCh produced a sustained reduction in I sc , rather than a diminished transient increase in I sc observed in other models, such as those evoked by 2,4,6-trinitrobenzenesulfonic acid, 2,4-dinitrobenzenesulfonic acid (21,34), or oxazolone (unpublished observation). Underlying differences in the models may contribute to this discrepancy; for example, 2,4,6-trinitrobenzenesulfonic acid and 2,4-dinitrobenzenesulfonic acid elicit a polarized Th1-type inflammatory response and oxazolone produces a Th2-type response, whereas DSSinduced colitis involves a Th1-and a Th2-type inflammatory profile (reviewed in Ref.…”
Section: Discussionsupporting
confidence: 77%
“…In normal mammalian colon, the ion transport response to ACh or to synthetic derivatives (e.g., CCh) is dominated by activation of epithelial M 3 cholinergic receptors, the ligation of which causes a Cl Ϫ efflux from the cell (8,38). We previously showed that cholinergic control of ion transport is perturbed in tissue from mice with DSS-induced colitis (38), complementing observations from other studies (21,34). However, the DSS model is intriguing, because CCh produced a sustained reduction in I sc , rather than a diminished transient increase in I sc observed in other models, such as those evoked by 2,4,6-trinitrobenzenesulfonic acid, 2,4-dinitrobenzenesulfonic acid (21,34), or oxazolone (unpublished observation).…”
Section: Discussionsupporting
confidence: 52%
“…RT-PCR was conducted as previously described (27) to determine the expression of PAR-1 mRNA in mouse colon. Expression of the housekeeping gene GAPDH was assessed as an internal control.…”
Section: Rt-pcrmentioning
confidence: 99%
“…The reaction mixture contained 5 l of 10ϫ PCR buffer, 1 l of 10 mM dNTP, 2 l of each of the 5Ј and 3Ј primers, 0.5 l of HotStartTaq DNA polymerase (Qiagen), 2 l of the cDNA template, and 38 l of DEP-treated H 2O (Invitrogen). The primer sequences used for PAR-1 amplification were 5Ј-ATGGGGCCGCGGCGGCT-GCT-3Ј and 5Ј-GGGCTGGTCAGATATCCGGA-3, whereas those used for GAPDH amplification were 5Ј-CGGAGTCAACGGATTT-GGTCGTAT-3Ј and 5Ј-AGCCTTCTCCATGGTGGTGAAGAC-3Ј (27). PCR for PAR-1 was stopped after 42 cycles (denaturation at 94°C for 1 min, annealing at 54°C for 1 min and elongation at 72°C for 1 min).…”
Section: Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation